Law and Opera (Springer International Publishing, 2018)
This book explores the various connections between Law and Opera, providing a comprehensive, multinational, and multidisciplinary (with approaches from jurists, philosophers, musicologist, historians) resource on the subject. Further, it makes a valuable contribution to studies on law and the humanities. While, for example, the relationship between law and literature has been extensively researched, the relationship between Law and Opera remains largely overlooked. The book approaches the topic from three perspectives in three main sections: Law in Opera, Law on Opera, and Law around Opera.